Simultaneous Bilateral Rupture of the Patellar Tendon and Medial Collateral Ligament: A Case Report and Literature Review - Jean G. Louka; Damien Pourre (Case Reports in Orthopedics)
Bilateral rupture of the patellar tendon is considered an uncommon and rare musculoskeletal injury. The association of this lesion with medial collateral ligament tear appears to be exceedingly rare. We present the case of a combined rupture of the medial collateral ligament (MCL) and the patellar tendon of both knees in a 48-year-old man, after falling 2 meters down an embankment. While there are numerous publications concerning associated MCL tears and other knee ligaments, a combination of MCL tear with a patellar tendon rupture is very rare. In addition, our case presents the first case recorded in the literature, involving both knees of a patient. The clinical case is described and discussed following a review of the literature. The symmetrical knee injury was treated with a primary direct repair of the MCL tears and using a suture anchor fixation of the patellar tendon ruptures, which was reinforced by a stainless steel wire and an autograft of the ipsilateral quadriceps tendon.